Quality Management of Frontier, Outermost and Disadvantaged Schools in Improving Achievement In Junior Secondary Schools - Ririn Angreany; Husnul Madihah; Didi Susanto (STAI Serdang Lubuk Pakam, 2023)
This study aims to analyze the quality management of frontier, outermost and disadvantaged schools in improving school achievement, the focus of research on planning, implementation, organization, and evaluation. This research was conducted at SMPN 7 Dusun Selatan and SMPN Satu Atap 1 Dusun Selatan, South Barito Regency, Central Kalimantan. The research method used is qualitative, with data collection techniques of observation, interviews, and documentation studies. The results of the study revealed that (1) Planning for the Implementation of Quality Standards in Schools has been carried out with an understanding and method in accordance with quality management standards and planned; 2) Implementation of the implementation of quality standards in schools has been carried out with guidance, strategies, time and place, measured in accordance with quality management standards; 3) Organizing the implementation of quality standards in schools is carried out with management procedures and structured according to the field of education units; 4) Evaluation of the implementation of quality standards in schools is carried out consistently. This research has implications for improving the quality of education, especially in disadvantaged areas.